ChemInform Abstract: Broensted Acid‐Promoted Formation of Stabilized Silylium Ions for Catalytic Friedel—Crafts C—H Silylation. Issue 50 (November 2016) - Chen, Qing‐An; Klare, Hendrik F. T.; Oestreich, Martin
Abstract: The protocol represents a convenient way for the regioselective introduction of silyl groups onto N‐methyl indole and aniline derivatives.